Occupational exposure of healthcare and research staff to static magnetic stray fields from 1.5–7 Tesla MRI scanners is associated with reporting of transient symptoms - Schaap, Kristel (BMJ Publishing Group, 2014)
OBJECTIVES: Limited data is available about incidence of acute transient symptoms associated with occupational exposure to static magnetic stray fields from MRI scanners. We aimed to assess the incidence of these symptoms among healthcare and research staff working with MRI scanners, and their association with static magnetic field exposure. METHODS: We performed an observational study among 361 employees of 14 clinical and research MRI facilities in The Netherlands. Each participant completed a diary during one or more work shifts inside and/or outside the MRI facility, reporting work activities and symptoms (from a list of potentially MRI-related symptoms, complemented with unrelated symptoms) experienced during a working day. We analysed 633 diaries. Exposure categories were defined by strength and type of MRI scanner, using non-MRI shifts as the reference category for statistical analysis. Non-MRI shifts originated from MRI staff who also participated on MRI days, as well as CT radiographers who never worked with MRI. RESULTS: Varying per exposure category, symptoms were reported during 16–39% of the MRI work shifts. We observed a positive association between scanner strength and reported symptoms among healthcare and research staff working with closed-bore MRI scanners of 1.5 Tesla (T) and higher (1.5 T OR=1.88; 3.0 T OR=2.14; 7.0 T OR=4.17). This finding was mainly driven by reporting of vertigo and metallic taste. CONCLUSIONS: The results suggest an exposure-response association between exposure to strong static magnetic fields (and associated motion-induced time-varying magnetic fields) and reporting of transient symptoms on the same day of exposure. TRIAL REGISTRATION NUMBER: 11-032/C